Oral hygiene of hospitalized patients and nursing care: a literature review - Kohatsu, Deborah; Mathiolli, Carolina; Coldibelli, Ligia Maria Ferreira; Lago, Milena Torres Guilhem; Andrade, Ariane Thaise Alves Monteiro de (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 37 No especial (2021): Enfermagem, 2021)
Objective: to analyze through the scientific literature, what are the consequences that poor oral hygiene can have on hospitalized patients and relate nursing care to this care. Methods: This is a bibliographic search using the SciELO and LILACS databases, from the years 2008 to 2019, in which 16 articles were selected according to the pre-established inclusion criteria. Results: Three categories emerged: Oral hygiene and the consequences of impaired care, Knowledge of nursing in relation to oral hygiene and Nursing care and its importance in care. Conclusion: Performing oral hygiene in hospitalized patients is the responsibility of nursing, such as prescription, execution and evaluation of results, however, hospital institutions do not have the elaboration of protocols and training that standardize this care as routines to obtain good satisfaction in the search for improvements in health care.